PENGGUNAAN TEKNOLOGI DALAM MENINGKATKAN KETERAMPILAN SISWA SD DI ABAD 21 - Kurnia Permata Nur Aisah; Yustina Trihartatik; Dyah Ayu Permatasari; Ngurah Ayu Nyoman (STKIP Subang, 2025)
The aim of this research is to study the efectivity of tecnology using on developing elementary students’ skills. Learning method which is integrated with digital technology such as computer, tablet, and education application are hoped can improve learning motivation, concept understanding, skill to think critically, and also students’ creativity. This reasearch has aim to identity ways to use technology on improving elementary students’ skills, especially 21st century skills which cover skill to think critical, creativity, collaboration, and communication. The research result can give contribution on improving effective learning model by using tecnology potential on improving education quality in elementary school.